Expression of p63, p53 and Ki-67 in Patients with Cervical Intraepithelial Neoplasia - Androniks MITILDZANS; Anastasija ARECHVO; Dace REZEBERGA; Sergejs ISAJEVS (Federation of Turkish Pathology Societies, 2017)
Objective: Cervical intraepithelial neoplasia (CIN) is a dysplastic process in cervical squamous epithelium and carries a risk of progression to cervical cancer. The aim of this study was to compare expression of three biomarkers named p53, p63 and Ki-67 in patients with various grades of cervical intraepithelial neoplasia and in a control group. Material and Method: 58 patients were enrolled in the study. Each patient underwent a colposcopy-guided biopsy of the cervix. Immunostaining for markers (p53, p63 and Ki-67) was performed on tissue samples of normal cases (n=10), CIN I (n=20), CIN II (n=14), and CIN III (n=14). Results: Our study showed a significant increase of the expression of the analyzed biomarkers in most patients with CIN III compared to CIN II and CIN I. Furthermore, p53 and p63 were significantly increased in CIN I compared to the control group. Conclusion: The expression of Ki-67, p63 and p53 differed between CIN I, CIN II and CIN III. p63 and p53 were reliable biomarkers to distinguish reactive changes from CIN I, while all three biomarkers (Ki-67, p53 and p63) had a high degree of sensitivity and specificity to distinguish between CIN III, CIN II and CIN I.